2014
DOI: 10.30958/ajh.1-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Health Behavior among School-based Employees

Abstract: Employee health promotion programs increase work productivity and effectively reduce employer costs related to health care and absenteeism, and enhance worker productivity. Components of an effective worksite health program include stress management, exercise and nutrition and/or weight management classes or counseling. Few studies have documented correlates of health behaviors in school-based employees. A multi-component survey was used to examine relationships among stress, physical activity and specific foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…24 Gillan et al, showed that teachers with healthy food habits chose more task-oriented coping and regular physical activity was associated with less perceived stress and more effective coping. 25 Some studies in the developed countries have also utilized teachers as a vehicle to improve overall school health and designed national programs accordingly to target a broader audience of students. 26 Sorensen et al, demonstrated a positive effect of a school-based intervention designed to promote tobacco control among teachers in the Indian state of Bihar.…”
Section: Introductionmentioning
confidence: 99%
“…24 Gillan et al, showed that teachers with healthy food habits chose more task-oriented coping and regular physical activity was associated with less perceived stress and more effective coping. 25 Some studies in the developed countries have also utilized teachers as a vehicle to improve overall school health and designed national programs accordingly to target a broader audience of students. 26 Sorensen et al, demonstrated a positive effect of a school-based intervention designed to promote tobacco control among teachers in the Indian state of Bihar.…”
Section: Introductionmentioning
confidence: 99%
“… 25 Gillan et al , showed that teachers with healthy food habits chose more task-oriented coping and regular physical activity was associated with less perceived stress and more effective coping. 26 Some studies in the developed countries have also utilized teachers as a vehicle to improve overall school health and designed national programs accordingly to target a broader audience of students. 27 Sorensen et al , demonstrated a positive effect of a school-based intervention designed to promote tobacco control among teachers in the Indian state of Bihar.…”
Section: Introductionmentioning
confidence: 99%
“…25 Gillan et al, showed that teachers with healthy food habits chose more task-oriented coping and regular physical activity was associated with less perceived stress and more effective coping. 26 Some studies in the developed countries have also utilized teachers as a vehicle to improve overall school health and designed national programs accordingly to target a broader audience of students. 27…”
Section: Introductionmentioning
confidence: 99%